Learning of Nursing Students during the COVID-19 Pandemic: A Case Study in an Elementary Nursing Research Subject - Thailek, Tutchamat; Khamchan, Pranee; Thasaneesuwan, Samonnan (Journal of Research in Nursing-Midwifery and Health Sciences, 2023)
Objectives: This qualitative study aimed to explore the learning experience of nursing students studying an Elementary Nursing Research subject during the COVID-19 pandemic. Methods: The data were collected through focus group interviews from 25 nursing students. Trustworthiness was established in accordance with the Lincoln and Guba criteria. Results: The findings were composed of 4 themes: 1) learning from subject which consisted of 1.1) learning how to process research 1.2) learning how to search for credible empirical evidence and mastering the citation skills 1.3) learning teamwork skills 1.4) learning systematic work skills, and 1.5) learning to practice using the English language more frequently 2) The findings regarding success in studying research were 2.1) self-responsibility 2.2) help from friends 2.3) support from advisors 2.4) advice from senior students 2.5) patterns of teaching, and 2.6) modern learning materials. 3) The challenges encountered in the learning process were as follows: 3.1) lack of basic research knowledge and data analysis program 3.2) limited time 3.3) the internet connection was unreliable 3.4) difficulty in working, and 3.5) noise pollution. 4) The proposed problem-solving strategies to be employed in order to deal with the obstacles to the learning process in this course were as follows 4.1) group work 4.2) engaging in peer-assisted learning 4.3) self-study 4.4) provision of face-to-face classroom instruction, and 4.5) extending the duration of the course and simplifying the study contents. Conclusions: The results of this study can be used as a basis information that could prove useful in the management and development of other subject courses.